Institutional entrepreneurship: collaborative change in a complex Canadian organization. Issue 9 (18th November 2021) - Opara, Michael; Okafor, Oliver Nnamdi; Ufodike, Akolisa; Kalu, Kenneth
Abstract : Purpose: This study adopts an institutional entrepreneurship perspective in the context of public–private partnerships (P3s) to highlight the role of social actors in enacting institutional change in a complex organizational setting. By studying the actions of two prominent social actors, the authors argue that successful institutional change is the result of dynamic managerial activity supported by political clout, organizational authority and the social positioning of actors. Design/methodology/approach: The authors conducted a field-based case study in a complex institutional and organizational setting in Alberta, Canada. The authors employed an institutional entrepreneurship perspective to identify and analyze the activities of two allied actors motivated to transform the institutional environment for public infrastructure delivery. Findings: The empirical study suggests that the implementation of institutional change is both individualistic and collaborative. Moreover, it is grounded in everyday organizational practices and activities and involves a coalition of allies invested in enacting lasting change in organizational practice(s), even when maintaining the status quo seems advantageous. Originality/value: The authors critique the structural explanations that dominate the literature on public–private partnership implementation, which downplays the role of agency and minimizes its interplay with institutional logics in effecting institutional change. Rather, the authors demonstrate that, given the observed impact of social actors, public–private partnership adoption and implementation can be theorized as a social phenomenon.